2006
DOI: 10.1210/jc.2006-1281
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Lipid Metabolism in Small-for-Gestational-Age Infants at 72 Hours of Age

Abstract: In this study, SGA neonates displayed profiles suggestive of lower insulin sensitivity and less favorable lipid metabolism in the early postnatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
3
41
2
Order By: Relevance
“…By contrast, low TG levels found in LGA newborns would be the result of enhanced LPL activity derived from their increased adipose mass. Interestingly, in the pediatric literature there are also reports of high TG levels in the serum of SGA newborns taken a few days after delivery (23,24), especially in infants with a Ponderal index Ͻ10th percentile (24). This fits with our observations and suggests that SGA infants appear to have impaired utilization of circulating TGs, as a consequence of lacking peripheral adipose.…”
Section: Schaefer-graf and Associatessupporting
confidence: 90%
“…By contrast, low TG levels found in LGA newborns would be the result of enhanced LPL activity derived from their increased adipose mass. Interestingly, in the pediatric literature there are also reports of high TG levels in the serum of SGA newborns taken a few days after delivery (23,24), especially in infants with a Ponderal index Ͻ10th percentile (24). This fits with our observations and suggests that SGA infants appear to have impaired utilization of circulating TGs, as a consequence of lacking peripheral adipose.…”
Section: Schaefer-graf and Associatessupporting
confidence: 90%
“…Decreased body size could prompt an increase in ␤-cell mass, leading to increased insulin secretion in an attempt to normalize body size by promoting growth. A similar adaptive response may be seen in small-for-gestational-age humans, who manifest insulin levels 2.5-fold higher than controls (44), mirroring hyperinsulinemia in young FASDEL mice (Fig. 3A, bottom).…”
Section: Discussionsupporting
confidence: 65%
“…Some authors have suggested that IR, as a consequence of intrauterine growth retardation would be detectable as early as birth (7,8). On the other hand, there is evidence that increased insulin sensitivity induced by the fetal environment aims at ameliorating nutrient disposal and utilization, ultimately leading to fetal growth (9). In this respect, an increase in insulin sensitivity would be a physiological adaptation to fetal growth restriction because insulin is a major regulator of fetal growth.…”
Section: Introductionmentioning
confidence: 99%